Natural resource management philosophy: Sustainability principles in forest area management local community-based - Titisari, Andari; Zahra, Nabila Fathia (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: The application of philosophy in natural resource management provides a solid foundation for making wise and sustainable decisions. Forests are a source of livelihood for people, especially in developing countries including Indonesia. Policies that favor the fulfillment of human needs without damaging the environment are based on the philosophy of environmental ethics and sustainability. Each country has different policies in managing forest areas, including involving local communities. Methods: This article analyzes community-based forest area management implemented by a number of countries such as Indonesia, Thailand, Myanmar, Bangladesh, Canada, and Mexico. This article also examines the application of the concept of collaboration and a stronger role of the private sector in other countries. The in-depth analysis in this article uses literature and case studies from Indonesia, Thailand, Myanmar, and Bangladesh. Canada, the United States, and South Korea. Findings: The article's conclusion highlights that sustainable natural resource management hinges on applying philosophical principles, particularly environmental ethics and sustainability, to policy-making. It emphasizes that community involvement and robust governance are key to successful forest conservation efforts, as shown by various case studies and management models. Conclusion: Forest management is greatly influenced by the relationship between state capacity and social capital, in this case community participation. If the capacity of the state is weak, while social capital is weak, then the concept of community-based forest management can be carried out. Novelty/Originality: The rehabilitation of an area of 410 ha into rubber plantations managed by local residents has brought in new sources of income. From 2010 to 2017 the Gini coefficient of inequality decreased from 34.6% to 31.3%.